Surveillance Aircraft and the Borders of Schengen. Issue 1 (April 2020) - Novotný, Vít
There is a widespread perception that the development of surveillance technologies in border management is antagonistic to civil liberties. This article attempts to contribute to a better understanding of the need for new technological means to survey the EU's external border. Contrary to the critics, it contends that there is no liberty without security. It argues that the so-called militarisation of the EU's borders is a precondition for countering the dangers which threaten our liberties. These dangers include organised cross-border crime, illegal migration and incursions by hostile powers. The article also demonstrates that the use of border surveillance aircraft contributes to saving lives at the EU's external border and that the use of modern technologies generates record trails which make it easier to track potential human rights abuses committed by border guards. To manage migration, facilitate legitimate commerce, monitor for illegal waste dumping and guarantee the undisturbed functioning of our institutions, improved border management with the help of modern technologies is a necessity.